Reflectance confocal microscopy as a useful diagnostic tool for monitoring of skin containing vascularized composite allograft rejection: A preliminary study on rats. Issue 2 (11th May 2015) - Zor, Fatih; Karagoz, Huseyin; Erdemir, Asli Turgut; Karslioglu, Yildirim; Acikel, Cengiz Han; Kapaj, Rezarta; Guzey, Serbulent; Gurel, Mehmet Salih; Isik, Selcuk; Siemionow, Maria
Abstract : Vascularized composite allografts can undergo immune‐mediated rejection, and skin biopsies are needed for monitoring of the transplant. However it is an invasive method, and requires processing time and pathological assessment. The purpose of this study is to use a new noninvasive monitoring method of the reflectance confocal microscopy (RCM) to determine severity of the allograft rejection on rats. Five groin flap allotransplantation were performed between 10 male Sprague‐Dawley rats. Immunosuppressive therapy with cyclosporine A was given to the recipients during 10 days after surgery and was ended at the 10th postoperative days to allow acute transplant rejection. Following cessation of CsA, concomitant RCM evaluation and skin biopsy was performed every other day from each animal until total rejection of the allograft. Complete rejection of the allograft took nearly about 10 days and 4 or 5 RCM evaluation and skin biopsy was performed from each rat during this period. A total of 17 specimens were evaluated. A scoring system was developed based on the RCM findings. Skin biopsies were evaluated according to the Banff 2007 working classification criteria. RCM evaluation revealed epidermal irregularity and collagen destruction, however mild perivascular inflammation and degeneration of the basal epidermal layer were observed in early and late rejection period respectively with histopathologic evaluation. High correlation was found between the RCM scores and histopathologic grading. The RCM may be the useful tool to reduce the need for skin biopsy for monitoring of the skin containing vascularized composite allograft. © 2015 Wiley Periodicals, Inc. Microsurgery 36:144–151, 2016.